Nilai Estetis Pada Puisi “Sawah” Karya Sanusi Pane dengan Pendekatan Stilistika - Sri Silfiani (Concept: Journal of Social Humanities and Education, 2022)
This study will discuss the analysis of aspects contained in the poem "Sawah" by Sanusi Pane using a stylistic approach. The analyzed aspects are language style, diction, figure of speech, and imagery to determine the aesthetic value and foster a national sense of the poem. The method used in this study is a qualitative descriptive method with a stylistic approach. The style of language, diction, figure of speech, and the imagery of a literary work are born from one's thoughts through the steps of contemplation and appreciation of something. In literary works, aesthetic value is a value based on the beauty that previous visitors have made with the work. In the poem "Sawah" by Sanusi Pane, the author uses a lot of language style and connotative meanings in his poetry which aims to assess the aesthetics or meaning contained in each line.